Penguatan Pendidikan Karakter Melalui Projek P5 Berbasis Seni Wayang Orang di SMKI Yogyakarta - Asy'ari , Farosya; Anzaki Wakhid Nur Rohman (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2025)
Education has a strategic role in strengthening the nation's character amidst the challenges of globalisation. The preservation of local wisdom is one of the important means in shaping the character of the younger generation. This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) based on the performing arts of wayang orang titled Semar Mbangun Desa in strengthening character education at SMKI Yogyakarta. This research uses a descriptive qualitative approach with data collection techniques through interviews, observation, documentation, and field notes. The results showed that wayang orang performance activities within the framework of P5 were able to instil character values that were in line with the dimensions of the Pancasila Student Profile, such as mutual cooperation, critical reasoning, creativity, and noble character. Wayang orang is not only a medium for cultural preservation, but also an actualisation space for students to develop their potential, understand the nation's culture, and strengthen national identity. In conclusion, the implementation of P5 based on traditional arts such as wayang orang at SMKI Yogyakarta has proven effective in strengthening character education while preserving local cultural heritage